Dyslexia and the magnocellular-parvocellular coactivaton hypothesis. (February 2021) - Ciavarelli, Ambra; Contemori, Giulio; Battaglini, Luca; Barollo, Michele; Casco, Clara
Abstract: Previous studies showed that the lateral masking of a fast-moving low spatial frequency (SF) target was strong when exerted by static flankers of lower or equal to the target SF and absent when flankers' SF was higher than the target's one. These masking and unmasking effects have been interpreted as due to Magnocellular-Magnocellular (M-M) inhibition and Parvocellular-on-Magnocellular (P-M) disinhibitory coactivation, respectively. Based on the hypothesis that the balance between the two systems is perturbed in Developmental Dyslexia (DD), we asked whether dyslexic children (DDs) behaved differently than Typically Developing children (TDs) in conditions of lateral masking. DDs and TDs performed a motion discrimination task, of a .5c/deg Gabor target moving at 16 deg/sec, either isolated or flanked by static Gabors with a SF of .125, .5 or 2 c/deg (Experiment 1). As a control, they also performed a contrast detection task of a static target, either isolated or flanked (Experiment 2). DDs did not perform any different from TDs with either a static target or an isolated moving target of low spatial frequency, thus suggesting efficient feedforward Magnocellular (M) and Parvocellular (P) processing. Also, DDs showed similar contrast thresholds to TDs in the M-M inhibition condition. Conversely, DDs did not recover from lateral masking in the M-P coactivation condition. In addition, their performance in this condition negatively correlated with non-words accuracy, supporting the suggestion that an inefficient Magno-Parvo coactivation may possibly be associated to both higher visual suppression and reduced perceptual stability during reading.